Економіко-статистичне забезпечення стратегій розвитку підприємницької діяльності в електронній комерції - Ткаченко, А.М.; Демченко, О.М. (Управління економікою: теорія та практика, 2025)
У статті розглянуто науково-практичні підходи до формування стратегій розвитку підприємницької діяльності в електронній комерції з урахуванням інструментів економічної статистики. У емпіричній частині статті здійснено статистичний аналіз динаміки розвитку електронної комерції в Україні за останні роки, зокрема в умовах багаторівневої кризи. Окрему увагу приділено рекомендаціям для бізнесу, державної політики та науковців щодо інтеграції економічної статистики у процес стратегічного управління. Аргументовано, що без застосування сучасних статистичних підходів неможливо ефективно конкурувати в умовах високої динаміки цифрової економіки. The article explores theoretical, methodological, and practical aspects of using economic statistics to develop strategies for the growth of entrepreneurial activity in e-commerce. In the context of global digitalization, e-commerce has evolved into a full-fledged business model. In such an environment, enhancing enterprise competitiveness through effective data utilization becomes critically important. The aim of the study is to substantiate the role of economic statistics as a foundation for the formation and implementation of development strategies for entrepreneurial activity in the digital domain. The theoretical section reviews the essence of economic statistics, its functions in the digital economy, the characteristics of e-commerce as a business model, and modern approaches to assessing enterprise competitiveness. The empirical part presents a statistical analysis of the current state and dynamics of e-commerce in Ukraine for 2024–2025, based on real indicators such as total online sales, average order value, share of online channels in the retail sector, and digital readiness of the population. Ukraine demonstrates rapid e-commerce growth, although it still lags behind more digitally mature markets. A methodology for integrating economic-statistical tools into strategic business management is proposed. It includes the collection and processing of data, the formation of a statistical panel, competitiveness index construction, regression analysis, and strategic monitoring. A real-life case illustrates how data-driven decision-making led to measurable growth in market share and profitability. The article also provides recommendations for businesses, public policy, and academic research regarding the use of economic statistics in the digital economy. The findings underline the necessity of incorporating data analytics into strategic planning to ensure competitiveness in fast-changing e-commerce environments.